九州圏内の救命救急センターに所属する看護師の代理意思決定支援の実践状況と関連要因 - 本田 智治; 石松 祐二; 辻 麻由美; 大山 祐介; 吉田 浩二 (日本看護科学会誌, 2024)
要旨　目的：九州圏内の救急領域の看護師における代理意思決定支援の実践状況とその実践に関連する要因を明らかにする．　方法：九州圏内の救命救急センター看護師603名に対し，救急・集中治療領域の終末期治療における代理意思決定支援実践尺度を含めた質問紙調査を行った．代理意思決定支援実践尺度を従属変数として解析した．　結果：分析対象者は123名とした．重回帰分析の結果，代理意思決定支援には道徳的感受性（β＝.296，p＜.001），看護師経験年数（β＝-.203，p＝.021），代理意思決定支援の困難感（β＝-.183，p＝.033），看護師有資格者からの支援体制（β＝.189，p＝.032）が関連していた．　結論：代理意思決定支援実践には，道徳的感受性，看護師経験年数，代理意思決定支援の困難感，専門看護師や認定看護師など有資格者からの支援体制が関連していた． 　Objective: The purpose of this study was to assess surrogate decision-making support by nurses in the emergency medical field in the Kyushu area, and to clarify the related factors to it.　Methods: A questionnaire was conducted among 603 nurses in an emergency and critical care center in the Kyushu, Japan area. The survey items included a nursing practice scale for measuring support for surrogate decision-makers of terminal care in the intensive and critical care unit. A statistical analysis was conducted using the surrogate decision-making support practice scale score as the dependent variable and the other items as independent variables.　Results: There were 123 subjects in the analysis. A multiple regression analysis revealed that moral sensitivity(β=.296, p＜.001), years of nursing experience(β=-.203, p=.021), difficulties with surrogate decision-making support(β=-.183, p=.033), and support from qualified nurses(β=.189, p=.032) related to the practices surrogate decision-making support.　Conclusion: The results showed that moral sensitivity, years of nursing experience, difficulties with surrogate decision-making support, and support from qualified nurses related to the practices associated with surrogate decision-making support.